Phylogenetic relationship of Gram Negative Bacteria of Enterobacteriaceae Family in the Positive Widal Blood Cultures based on 16S rRNA Gene Sequences - Darmawati, Sri; Sembiring, Langkah; Asmara, Widya; Artama, Wayan T.; Kawaichi, Masashi (Indonesian Journal of Biotechnology, 2014)
The purpose of this study was to analyze the phylogenetic relationship of Gram negative bacteria (3strains of Salmonella typhi, 1 strain of Escherichia coli, 1 strain of Serratia marcescens, and 3 strains of Enterobactercloacae) of Enterobacteriaceae family in positive Widal blood cultures based on 16S rRNA gene sequences. Theresults respectively showed that each two 16S rRNA gene clones of Serratia marcescens KD 08.4 had a closerelationship with 16S rRNA gene of Serrratia marcescens ATCC 13880 (similarity: 99.53-99.8%), Eschericia coliBA 30.1 with Eschericia coli ATCC 11775T (similarity: 99.38-99.67%), Salmonella typhi BA 07.4, Salmonella typhiKD 30.4, and Salmonella typhi SA 02.2 with Salmonella typhi ATCC 19430T (similarity: 99.4-100%) as well as theisolates of Enterobacter cloacae SA 02.1, Enterobacter cloacae BA 45.4.1, one 16S rRNA gene clone of Enterobactercloacae TG 03.5 with Enterobacter cloacae ATCC 23373 (similarity: 99.0-99.87%).